LIFETIME PREVALENCE OF DSM‐IV MENTAL DISORDERS AMONG NEW SOLDIERS IN THE U.S. ARMY: RESULTS FROM THE ARMY STUDY TO ASSESS RISK AND RESILIENCE IN SERVICEMEMBERS (ARMY STARRS). Issue 1 (22nd October 2014) - Rosellini, Anthony J.; Heeringa, Steven G.; Stein, Murray B.; Ursano, Robert J.; Chiu, Wai Tat; Colpe, Lisa J.; Fullerton, Carol S.; Gilman, Stephen E.; Hwang, Irving; Naifeh, James A.; Nock, Matthew K.; Petukhova, Maria; et al.
<x xml:space="preserve">Abstract</x> Background The prevalence of 30‐day mental disorders with retrospectively reported early onsets is significantly higher in the U.S. Army than among socio‐demographically matched civilians. This difference could reflect high prevalence of preenlistment disorders and/or high persistence of these disorders in the context of the stresses associated with military service. These alternatives can to some extent be distinguished by estimating lifetime disorder prevalence among new Army recruits. Methods The New Soldier Study (NSS) in the Army Study to Assess Risk and Resilience in Servicemembers (Army STARRS) used fully structured measures to estimate lifetime prevalence of 10 DSM‐IV disorders in new soldiers reporting for Basic Combat Training in 2011–2012 (n = 38, 507). Prevalence was compared to estimates from a matched civilian sample. Multivariate regression models examined socio‐demographic correlates of disorder prevalence and persistence among new soldiers. Results Lifetime prevalence of having at least one internalizing, externalizing, or either type of disorder did not differ significantly between new soldiers and civilians, although three specific disorders (generalized anxiety, posttraumatic stress, and conduct disorders) and multimorbidity were significantly more common among new soldiers than civilians. Although several socio‐demographic characteristics were significantly associated with disorder prevalence and persistence, these associations were uniformly weak. Conclusions New soldiers differ somewhat, but not consistently, from civilians in lifetime preenlistment mental disorders. This suggests that prior findings of higher prevalence of current disorders with preenlistment onsets among soldiers than civilians are likely due primarily to a more persistent course of early‐onset disorders in the context of the special stresses experienced by Army personnel.